Effect of Genetic Type and Sex on Reproductive, Growth, Survival Performance and Thermal Tolerance Index of the Local Chicken (Gallus gallus) of the Western Highlands of Cameroon - Keambou , T.C.; Hako, B.A.; Bembide, C.; Emma, P.J. Ngono; Manjeli, Y. (International Journal of Poultry Science, 2013)
Reproductive performance of local chicken from the Western Highlands of Cameroon has been significantly influenced by the genetic type, the naked neck chicken displaying the best laying performance. Fertility rate was higher (P<0.05) in rural (64.2%) than urban (43.5%) areas but the hatching rate were comparable (62.3 and 59.7%). The feathered tarsus chicken got the highest body weight (P<0.05) throughout the test. Within each breed, the males were significantly (P<0.01) heavier than females regardless of age. The growth rate of local chicken was significantly influenced (P<0.05) by the genetic type from hatching to week 4 and very significantly (P<0.01) between the 4th and 16th week. The genetic type of local chicken significantly influenced (P<0.05) the feed efficiency during the period 12-16 weeks, while the sex effect on this parameter was very significant during the period from 8th to 12th week, whereas the interaction of these two sources of variation was not significant regardless of the period. Feathered tarsus chickens were less resistant, having only 61.4% of survived chicks. On the contrary, the normal feathering chickens were the most rustic, with 85.6% survival rate.